2010
DOI: 10.1111/j.1365-2990.2010.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

The myotonic dystrophy type 2 (DM2) gene product zinc finger protein 9 (ZNF9) is associated with sarcomeres and normally localized in DM2 patients' muscles

Abstract: (2010) Neuropathology and Applied Neurobiology 36, 275-284 The myotonic dystrophy type 2 (DM2) gene product zinc finger protein 9 (ZNF9) is associated with sarcomeres and normally localized in DM2 patients' muscles Aims: Myotonic dystrophy type 2 (DM2) is caused by a [CCTG]n intronic expansion in the zinc finger protein 9 (ZNF9) gene. As for DM1, sharing with DM2 a similar phenotype, the pathogenic mutation involves a transcribed but untranslated genomic region, suggesting that RNA toxicity may have a role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
(60 reference statements)
1
17
0
Order By: Relevance
“…[31][32][33][34][35] This is consistent with our findings in normal controls, where overall ZNF9 expression is higher in slow type 1 fibers than in fast type 2 fibers and early differentiating myocytes (data not shown). However, the localization of ZNF9 changing from the nuclei in undifferentiated myoblasts to the cytoplasm during differentiation to myotubes and the cytoplasmic localization of ZNF9 in mature human muscle fibers in sarcomeric striations at the Z-disks 36 is unexpected for a transcription factor and suggestive of other functions in mature muscle fibers. In fact, ZNF9 has recently been implicated in the regulation of cap-dependent and -independent translation.…”
Section: Discussionmentioning
confidence: 93%
“…[31][32][33][34][35] This is consistent with our findings in normal controls, where overall ZNF9 expression is higher in slow type 1 fibers than in fast type 2 fibers and early differentiating myocytes (data not shown). However, the localization of ZNF9 changing from the nuclei in undifferentiated myoblasts to the cytoplasm during differentiation to myotubes and the cytoplasmic localization of ZNF9 in mature human muscle fibers in sarcomeric striations at the Z-disks 36 is unexpected for a transcription factor and suggestive of other functions in mature muscle fibers. In fact, ZNF9 has recently been implicated in the regulation of cap-dependent and -independent translation.…”
Section: Discussionmentioning
confidence: 93%
“…An equal amount of protein was loaded per lane and electrophoresed on 12% sodium dodecyl sulfate–polyacrylamide gels, and then transferred to nitrocellulose Protran membranes (Schleicher & Shuell GmbH). After blocking non specific sites in TrisHCl buffer pH 7.5 (TBS) containing 5% BSA for 30 min at 42°C, membranes were incubated overnight at 4°C with rabbit polyclonal anti-CUGBP1-posphoS28 (Abnova; 0.5 µg/ml), with mouse monoclonal anti CUGBP1 (Santa Cruz; clone 3B; 1∶1000), or with rabbit polyclonal anti-ZNF9/CNBP (1∶1000) [45]. After several washes in TBS+0.2% Tween20 or TBS+0.3% Tween20, membranes were incubated with horseradish peroxidase-conjugated goat anti-mouse or anti-rabbit secondary antibodies (Jackson ImmunoResearch Laboratories) diluted 1∶5000 or 1∶10000 in TBS+5% BSA+ 0.2% Tween20 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned previously, CELF1 protein levels increase in DM and CELF1 overexpression in transgenic mice inhibits myogenesis and causes MEF2A and p21 overexpression (Timchenko et al, 2004). Several studies have suggested that DM2 is caused by CNBP haploinsufficiency (Chen et al, 2007; Huichalaf et al, 2009; Raheem et al, 2010) although other groups report that CNBP protein levels are not altered in this disease (Botta et al, 2006; Margolis et al, 2006; Massa et al, 2010). Interestingly, CNBP binds to the 5′ UTRs of terminal oligopyrimidine (TOP) genes encoding a variety of proteins important for translational regulation, including PABPC1, eIF1a and eIF2, so CCUG exp expression has been proposed to impact the rate of global protein synthesis (Huichalaf et al, 2009; Schneider-Gold & Timchenko, 2010).…”
Section: 2 Rna Toxicity and Protein Sequestration In Myotonic Dystrmentioning
confidence: 99%